Analisis In-Silico Struktur Tiga Dimensi Reseptor Trk A dan Trk B Protein Neurotrophin 3 Pada Gallus gallus (Chicken) - Muhammad F. Rahman; Amiruddin Kasim; Muchlis L. Djirimu; I. Made Budiarsa (Jurnal Biologi Papua, 2020)
NT3 protein is expressed by Neurotrophin 3 (NTF-3) which plays a role in the process of differentiation, survival of peripheral and neuropathological of neurons. The information of structure and function of NT-3 proteins is still very limited, especially in Gallus gallus. This study aims to predict the three-dimensional structure of the Trk A and Trk B proteins in Gallus gallus. The target protein obtained from the UniProt server with access codes Q91009 (Trk A) and Q91987 (Trk B) using the 6kzc 1.A (PDB ID) template was analyzed in silico through a homology approach and describing the structural assessment using Chimera UCSF software. The analysis showed that the Trk A protein had a QMEAN value of -0.08, composed of 778 amino acids, mass 87334.30 Daltons, and Seq Identity 79.93%. Trk B had a QMEAN value of 0.16, consisting of 818 amino acids, mass 91732.05 Daltons, and Seq Identity 84.30%. Key words: NT3; homology; UCSF chimera; G. gallus